Tingkat Kepatuhan Penggunaan Obat Anti Tuberkulosis Pada Pasien Di Puskesmas Tombulilato Kabupaten Bone Bolango - Amran, Rosmala; Abdulkadir, Widysusanti; Madania, Madania (Jurusan Farmasi Universitas Negeri Gorontalo, 2021)
Tuberculosis is an infectious disease caused by the Mycobacterium tuberculosis bacterium. Compliance wiyh long-term medication is the key to tuberculosis control. It also has become a complex and dynamic phenomenon with various factors that are impactful on the patients' behavior of taking drugs. This non experimental observation research aims to measure the patients' compliance level of using anti-tuberculosis drugs in puskesmas (Community Health Center) Tombulilato. Relying on the cross-sectional design, this study collected the data from qualitative approach and employing the purposive sampling technique in selecting 38 respondents suffering from tuberculosis aged 15-75 years. Further, the collected data were processed using the SPSS program and were analyzed utilizing the univariate analysis. The results reveal that the respondents in the site area are categorized as â€œbeing compliantâ€ in using anti-tuberculosis drugs, with the percentage 86,8%.